"Do you want another baby after this?": How midwives discuss contraception with pregnant and postpartum women. (September 2022) - Tulloch, Melanie; Botfield, Jessica; Contziu, Hannah; Bateson, Deborah; Phipps, Hala; Wright, Sarah; McGeechan, Kevin; Black, Kirsten
Abstract : Discussing contraception is considered part of midwives' scope of practice in Australia, yet most midwives receive minimal training in conducting these discussions. There is a lack of guidance available in Australia on how and when midwives should discuss contraception with women, and little is known regarding midwives' experiences. As part of a larger study of midwife-led provision of contraceptive implants, we conducted semi-structured interviews with 13 hospital-based midwives and discussed their experiences of providing contraception information. Midwives perceived that most women found discussing contraception with a midwife to be highly acceptable, including those from cultural or religious backgrounds that may be stereotyped as being uninterested in contraception. Despite this, several midwives stated that due to the busy clinical environment, they tended to prioritise speaking to women they viewed to be most interested in postpartum contraception, including those of high parity, who had an unintended pregnancy, or were experiencing financial disadvantage or psychosocial stressors. Midwives' approaches to initiating contraception discussions varied widely. Most favoured introducing contraception into wider conversations about pregnancy spacing and women's plans for the future, in order to establish rapport and provide context to the discussion. Midwives felt that more than one conversation was necessary to allow women to consider the information before making a decision. Our findings suggest that most women are open to discussing contraception with a midwife, and that midwives are able to use different strategies to integrate these conversations into their practice. However, many women may still miss out on contraceptive information due to time pressures faced by midwives and cultural stereotypes that inform which women they prioritise for these discussions. National guidelines are needed that incorporate provision of contraception information as part of core midwifery practice, as well as provision of training and strategies to initiate and tailor contraception discussions to meet women's individual needs.